2016
DOI: 10.3389/fmicb.2016.01792
|View full text |Cite
|
Sign up to set email alerts
|

Culture-Based Screening of Aerobic Microbiome in Diabetic Foot Subjects and Developing Non-healing Ulcers

Abstract: The study was carried on diabetic foot patients to deduce clinical attributes, the occurrence of the range of aerobic microbial flora and to assess their comparative in vitro susceptibility to the customarily used antimicrobials. We also studied the potential risk factors involved in the development of non-healing ulcers. A total of 87 organisms were isolated from 70 specimens, including Escherichia coli (19.5%) among the Gram-negative and Staphylococcus aureus (18.4%) among the Gram-positive as the predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 27 publications
2
16
1
Order By: Relevance
“…Eight different species of bacteria were identified in total, varying from two to six different strains per subject (Fig 3b). This finding is consistent with data observed by other groups looking at this type of infection [16,17,48]. The culture conditions allowed us to isolate a variety of microorganisms.…”
Section: Diverse Microbiome Of a Grade 1b Ulcersupporting
confidence: 91%
“…Eight different species of bacteria were identified in total, varying from two to six different strains per subject (Fig 3b). This finding is consistent with data observed by other groups looking at this type of infection [16,17,48]. The culture conditions allowed us to isolate a variety of microorganisms.…”
Section: Diverse Microbiome Of a Grade 1b Ulcersupporting
confidence: 91%
“…There have been several studies regarding the microbiomes of skin surface lesions, particularly in skin diseases such as atopic dermatitis, acne and chronic wounds, the severity of which were found to be related to the degree of bacterial colonization . Focusing on the genus level, the relative abundance of Staphylococcus sequences is greater during disease flares compared with non‐lesional skin and is correlated with increased severity of atopic dermatitis, acne and rosacea; it has been suggested that skin inflammation affects the characteristics of bacterial communities .…”
Section: Discussionmentioning
confidence: 99%
“…This trend was similar to our study, in which patients with Pseudomonas in the “≥HCs” group had a higher level of IL-8. Interestingly, Pseudomonas aeruginosa were the predominant isolates of non-healing ulcers in diabetic foot patients ( 45 ), and diabetic foot infection has demonstrated higher concentrations of IL-6 and IL-1β than controls ( 46 ). Thus, Pseudomonas might be correlated to the inflammatory process in diabetic patients and might regulate the levels of cytokines.…”
Section: Discussionmentioning
confidence: 99%